Fiber-reinforced lime-based mortars: Effect of zeolite addition. (15th February 2015) - Liguori, B.; Caputo, D.; Iucolano, F.
Highlights: Hydraulic lime is a good alternative to cement in manufacturing repair mortars. Use of short fibers can reduce plastic shrinkage and improve durability of masonry. Zeolitic additions further improve mechanical performances of hydraulic mortars. Abstract: In a previous paper the authors demonstrated that adding glass fibers to hydraulic lime-based mortars leads to clear improvement in the post-cracking behavior. In order to enhance physical and mechanical performances of the above fiber reinforced mortars, the use of zeolitic addition was proposed. A phillipsite-rich tuff and a zeolite A [LTA] were selected and added in the mixtures. A significant decrease in open porosity and increase in mechanical behavior was achieved with each addition. In particular 20% of LTA produces an improvement of flexural and compressive strength up to 150% compared with fiber reinforced mortars without addition.